PENGARUH SISTEM OUTSOURCING DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT ASTRA INTERNATIONAL TBK AUTO 2000 - Maryam Dunggio; Rosario Rosario (Mediastima, 2020)
This study aims to analyze the effect of the work system outsourcing and compensation on the performance of employees in PT Astra International Tbk Auto 2000 body & paint using SEM-PLS analysis. Based on the results of data analysis, it is known that the application of work outsourced systems in accordance with the provisions and agreements between workers and companies has a positive and significant effect on employee performance. In addition, the provision of compensation in accordance with the conditions agreed upon between employees and the company has a positive and significant effect on employee performance.